Effects of Carotid or Vertebrobasilar Stent Placement on Cerebral Perfusion and Cognition - Moftakhar, Roham (AJNR Am J Neuroradiol, 2005)
INTRODUCTION: There are no well-established physiologic or neuropsychological criteria for identifying which patients with stenosis of the cervicocerebral vessels are at high risk of stroke or cognitive impairment. Our purpose was to evaluate changes in cognitive performance and cerebral perfusion associated with endovascular stent placement of the cervicocerebral vessels. METHODS: A consecutive series of 20 patients, 31–88 years of age, who underwent 21 stent procedures for arterial stenosis (10 extracranial carotid stents [ECS], four intracranial carotid stents [ICS], and seven extra- or intracranial vertebrobasilar stents [VBS]) was investigated retrospectively. All patients were evaluated with CT or MR perfusion studies both before and after stent placement. Cognitive response after stent placement was evaluated by using an informant questionnaire. RESULTS: In patients with anterior circulation stenoses (ECS and ICS group), 11 of 14 (79%) had a baseline perfusion abnormality and all 11 patients showed improved perfusion after stent placement. Four of seven (57%) patients with posterior circulation stenoses (VBS group) had a baseline perfusion abnormality and two of the four patients showed improved perfusion after stent placement. Degree of stenosis was the strongest predictor of the presence of a baseline perfusion abnormality (P = .03). Fifteen of 19 (79%) of the patients showed improved cognitive scores after stent placement. Among patients with improvement in perfusion after stent placement, 11 of 13 (85%) had improved cognitive scores. Improved perfusion after stent placement was a significant predictor of cognitive improvement (P = .04). Patients who were stented on an elective basis demonstrated greater improvement in cognition as compared with patients stented urgently (P = .01). CONCLUSION: Endovascular stent placement of the cervicocerebral vessels can safely and effectively resolve cerebral perfusion abnormalities. Improvement in perfusion parameters is associated with cognitive improvement. Larger, blinded, prospective studies are needed to confirm these preliminary observations.